ADVANTAGES OF FUZZY CONTROL. FUZZY CONTROLLER WITH TWO BASIC RULES - Ochilov Murodjon Ashirqulovich; Aralov G’ayrat Muhammadiyevich; Eshqobilov Sirojiddin Berdimurodovich (Galaxy International Interdisciplinary Research Journal, 2023)
Fuzzy logic is reminiscent of a human decision-making methodology. It deals with vague and inaccurate information. This is a gross simplification of real world problems based on degrees of truth rather than the usual true/false or 1/0 like Boolean logic. In other words, we can say that fuzzy logic is not fuzzy logic, but logic that is used to describe fuzziness. There can be many similar examples, with the help of which we can understand the concept of fuzzy logic.